A SINTESIS KITOSAN DARI CANGKANG KERANG DARAH (Anadara granosa) SEBAGAI BIOSENSOR UNTUK DETEKSI PESTISIDA MENGGUNAKAN MEMBRAN Au/KITOSAN - Pharnanda, Rossella; Prasetya, Predian Yudha; Handayani, Suci Tri; Fatehah, Aura Amalia; Basukiwardojo, Maria Monica Sianita (Unesa Journal of Chemistry, 2024)
Pesticides are chemicals that can kill or control pests. However, the current use of pesticides poses a threat to humans and the environment. This research aims to develop a biosensor with Au/Chitosan membrane electrode using chitosan from blood clam shell waste which has high sensitivity to pesticides, fast response time, and long-term stability. So as to achieve the target of Sustainable Development Goals (SDG's) 3, namely health and well-being. The method used is the preparation of blood clam shells, synthesis of chitosan from blood clam shells, making Au/Chitosan membrane electrodes, characterisation of pesticide detection biosensors. The results of FTIR testing of chitosan obtained a degree of deacetylation of 86.3202%. The successfully made Au/Chitosan membrane electrode has an optimum concentration of 5% with the best measurement at pH 7, deposition time of 5 seconds, and scan rate of 0.1 V/s.  Characterisation of carbamate pesticide detection biosensor using Au/Kitosan electrode shows that the Nernst factor obtained is 35.46 mV/decade, detection limit is 2x10 -8 M, measurement range is 10-8 M to 10-2 M, response time is 5-7 minutes, and precision with coefficient of variation for 10-4 M and 10-2 M concentration is 1.095% and 0.412% so that the Au/Chitosan membrane electrode can be used to detect carbamate pesticides effectively.